2007
DOI: 10.1038/sj.npp.1301480
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Neuropsychological Correlates of White Matter Abnormalities in Recent Onset Schizophrenia

Abstract: The objective of this study was to investigate the clinical and neuropsychological correlates of white matter abnormalities in patients with schizophrenia studied early in the course of illness. A total of 33 (21 male/12 female) patients with recent onset schizophrenia and 30 (18 male/12 female) healthy volunteers completed structural and diffusion tensor imaging exams. Patients also received clinical and neuropsychological assessments. Fractional anisotropy (FA) maps were compared between groups in the white … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
185
5
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(219 citation statements)
references
References 54 publications
28
185
5
1
Order By: Relevance
“…It is therefore of interest that the functional relevance of ErbB4Fvia its possible impact on the structural integrity of these fiber tractsFis further supported, ie externally validated, by our additional finding that FA was also related to RT which itself is frequently impaired in schizophrenia and which has been proposed to be an endophenotype of schizophrenia (Filbey et al, 2008). In this context, it is worth mentioning that several earlier studies have linked poor neurocognitive performance with reduced FA in frontotemporal fiber tracts (Szeszko et al, 2008). At the same time, our finding that the schizophrenia risk genotype predicts RT in the expected direction largely concurs with another study, which has reported ErbB4 genotype effects on neurocognitive measures in healthy controls (Nicodemus et al, 2006).…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…It is therefore of interest that the functional relevance of ErbB4Fvia its possible impact on the structural integrity of these fiber tractsFis further supported, ie externally validated, by our additional finding that FA was also related to RT which itself is frequently impaired in schizophrenia and which has been proposed to be an endophenotype of schizophrenia (Filbey et al, 2008). In this context, it is worth mentioning that several earlier studies have linked poor neurocognitive performance with reduced FA in frontotemporal fiber tracts (Szeszko et al, 2008). At the same time, our finding that the schizophrenia risk genotype predicts RT in the expected direction largely concurs with another study, which has reported ErbB4 genotype effects on neurocognitive measures in healthy controls (Nicodemus et al, 2006).…”
Section: Discussionsupporting
confidence: 49%
“…An increasing body of evidence from neuroimaging and postmortem studies also suggests that structural connectivity between brain regions is disturbed in schizophrenia and that altered myelination mayFin partFaccount for this deficit . In particular, the frequently made observation in functional imaging and electrophysiological studies that left frontotemporal connectivity might be preferentially affected in schizophrenic patients and their relatives has recently obtained support from several microstructural imaging studies Szeszko et al, 2008). However, it is currently unknown what molecular mechanisms may account for the deficiency of structural connectivity in schizophrenia illness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[40][41][42] Moreover, recent functional MRI studies have indicated that functional connectivity in the prefrontal cortex increases with the severity of psychotic symptoms, especially in the early stage of schizophrenia. 43,44 As functional hyperconnectivity may be reflected in regional FA increases, [40][41][42] our findings of both positive and negative associations with positive symptoms in 2 closely linked anatomical structures (AF and SLF) support the idea that psychotic symptoms arise from regional irregularities in white matter rather than deficits per se.…”
Section: Discussionmentioning
confidence: 99%
“…Several additional regions beyond the callosal body have been implicated in chronic schizophrenia including SLF (Rotarska-Jagiela et al, 2009;Rowland et al, 2009;Seok et al, 2007;Shergill et al, 2007;Szeszko et al, 2008) DMRI study in severe chronic schizophrenia L Holleran et al Jagiela et al, 2009;Seal et al, 2008), UF (Burns et al, 2003;McIntosh et al, 2008;Miyata et al, 2010;Mori et al, 2007b;Seal et al, 2008), internal capsule (Buchsbaum et al, 1998;Lim et al, 1999), external capsule (Rotarska-Jagiela et al, 2009;Seal et al, 2008), cingulum (Kubicki et al, 2003;Mori et al, 2007b;Seok et al, 2007;Sun et al, 2003;Wang et al, 2004), fornix (Fitzsimmons et al, 2009;Kuroki et al, 2006), anterior commissure (Choi et al, 2011), arcuate fasciculus (Burns et al, 2003;Phillips et al, 2009), and cerebellar peduncles (Okugawa et al, 2006;Seok et al, 2007). Differences in RD are less examined, yet to date increases have been detected in the external capsule (Seal et al, 2008), in the left inferior temporal and left occipital lobe (Ashtari et al, 2007), in temporal WM (Koch et al, 2011), and in the middle cerebellar peduncle (Okugawa et al, 2006), and increased mean diffusivity has been detected in the splenium of the corpus callosum (Foong et al, 2000).…”
Section: Discussionmentioning
confidence: 99%